Raw and steam exploded pine wood: Possible enhanced reactivity with gasification hydrogen. (5th October 2016) - Saeed, Muhammad Azam; Andrews, Gordon E.; Phylaktou, Herodotos N.; Gibbs, Bernard M.
Abstract: A commercial thermally treated biomass known as 'steam exploded biomass' or 'black pellets' was compared with the raw yellow pine wood feedstock to the process using the Hartmann dust explosion equipment. The aim was to investigate the difference in pulverised biomass reactivity and minimum explosible concentration, MEC. The reactivity was determined from the initial rate of pressure rise prior to the vent bursting in the Hartmann equipment. The flame speed in the vertical tube of the Hartmann equipment was also determined as a reactivity parameter. Steam exploded milled pellets (BP) was found to have a higher reactivity, leaner MEC and higher flame speed, than the raw pine. The enhanced reactivity of BP was due to the greater proportion of fine particles. Both raw pine and BP had a high reactivity for very rich mixtures and this was due to the gasification reactions in rich mixtures that released CO and hydrogen. The very lean MEC for both biomass also may have been enhanced by hydrogen release. Highlights: Reactivity of raw pine wood in comparison to its steam exploded pine wood. Fire and explosibility hazards and effect of steam explosion treatments. Possible role of hydrogen gasification for very lean MEC and enhanced reactivity of samples for rich concentrations. Surface morphological study of raw and steam exploded pine wood. Role of fine particles in the efficient flame propagation.